Blackness in opera - André, Naomi Adele; Bryan, Karen M. (Karen McGaha), 1954-; Saylor, Eric (University of Illinois Press, 2012)
"Blackness in Opera critically examines the intersections of race and music in the multifaceted genre of opera. A diverse cross-section of scholars places well-known operas (Porgy and Bess, Aida, Treemonisha) alongside lesser-known works such as Frederick Delius's Koanga, William Grant Still's Blue Steel, and Clarence Cameron White's Ouanga! to reveal a new historical context for re-imagining race and blackness in opera. The volume brings a wide-ranging, theoretically informed, interdisciplinary approach to questions about how blackness has been represented in these operas, issues surrounding characterization of blacks, interpretation of racialized roles by blacks and whites, controversies over race in the theatre and the use of blackface, and extensions of blackness along the spectrum from grand opera to musical theatre and film. In addition to essays by scholars, the book also features reflections by renowned American tenor George Shirley."--Publisher description.